Effect of mHealth, Interactive Voice Response System (IVRS) on Maternal and Fetal Outcomes - Manisha Malik, Vasim Raja Panwar, Shweta Mangal, Vaseem N Baig, Raja Babu Panwar, VM Katoch, Rajeev Gupta (RUHS Journal of Health Sciences, 2023)
Introduction: Pregnancy and child birth are universally celebrated events. The factors affecting the fetal outcome mainly lie within the premises of the antenatal period. The emergence of mobile telephone technology and its universal reach has improved service delivery, and information transfer. Thus, this study was planned to attempt improvement in the ante-natal care of pregnant women using an interactive voice response system (IVRS) with the ultimate aim of improving the maternal and fetal outcome, mainly in the form of low birth weight (LBW) rates. Methodology: The study was a community-based randomized intervention study. A total of 796 pregnant females of gestational age ≤16 weeks were recruited and followed up till delivery. The target population was from the urban slums of Jaipur. These areas are covered by Integrated Child Development Services (ICDS) scheme for the provision of basic child and maternal service. Results: Out of 796 recruited pregnant females, 722 singleton deliveries were analysed. 98.5% of pregnancy outcomes were in the form of live births and the rest were stillbirths. Among live births, 23.9% were low birth weight (21.4% in the intervention v/s 26.7% in the control area). A difference of 5% was observed in low birth occurrence between the two groups. Institutional deliveries were higher and caesarean sections, abortion, still birth, and congenital malformation among delivered were found to be lower in the intervention group as compared to the control group. The intervention group had a higher number of ANC visits and the difference was statistically significant. The maternal health indicators were slightly better in the intervention group. The number of iron-folic acid (IFA) tablets consumed and the number of pregnant females consuming them was also higher in the intervention group and was statistically significant. Conclusion: Intervention group as a result of intervention by mHealth and IVRS had better indicators of maternal and f